2014
DOI: 10.2147/cia.s66351
|View full text |Cite
|
Sign up to set email alerts
|

Walking in the high-rise city: a Health Enhancement and Pedometer-determined Ambulatory (HEPA) program in Hong Kong

Abstract: Due to the lack of good infrastructure in the public estates, many older adults in urban areas are sedentary. The Health Enhancement and Pedometer-Determined Ambulatory (HEPA) program was developed to assist older adults with diabetes and/or hypertension to acquire walking exercise habits and to build social support, while engaged in regular physical activity. This study aimed to describe the HEPA program and to report changes in participants’ walking capacity and body strength after 10-week walking sessions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In 102 older adults with obstructive lung disease, patients randomly assigned to use a pedometer had an increase of 3,080 steps, compared with a 140-step increase in the usual care group ( P <0.001) 30. A study from Hong Kong of 205 older adults who used a pedometer for 10 weeks found an increase in mean step count from 6,591 to 8,934 31. In a systematic review of seven articles with 484 total participants with musculoskeletal problems, the use of a pedometer increased the number of steps by an average of 1,950 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 102 older adults with obstructive lung disease, patients randomly assigned to use a pedometer had an increase of 3,080 steps, compared with a 140-step increase in the usual care group ( P <0.001) 30. A study from Hong Kong of 205 older adults who used a pedometer for 10 weeks found an increase in mean step count from 6,591 to 8,934 31. In a systematic review of seven articles with 484 total participants with musculoskeletal problems, the use of a pedometer increased the number of steps by an average of 1,950 3.…”
Section: Discussionmentioning
confidence: 99%
“… 30 A study from Hong Kong of 205 older adults who used a pedometer for 10 weeks found an increase in mean step count from 6,591 to 8,934. 31 In a systematic review of seven articles with 484 total participants with musculoskeletal problems, the use of a pedometer increased the number of steps by an average of 1,950. 3 Finally, a study using intensive counseling and educational intervention and a pedometer in 18 obese women aged >60 years showed an increase of 1,856 steps from baseline to 3 months and a decrease in weight.…”
Section: Discussionmentioning
confidence: 99%
“…Screening for malnutrition may also be helpful for this population. For those aged 80 or below and whose body height is lower than the average body height of their peers, a walking buddy programme with appropriate exposure to sunlight could be developed in a neighborhood, so that older adults could enjoy exercising regularly together in the sun (Leung et al., 2014). In Hong Kong, a population‐based frailty screening and prevention programme was carried out in 2017–2019, funded by the Hong Kong Jockey Club Charity Trust, targeting 9,000 people aged 50 or above (Cheng, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The physical environment may be of greater importance for certain populations in explaining total physical activity level. Many older adults have declined physical and cognitive capacity, reduced income, and less resources; hence, they are more vulnerable to the impact of physical environment on engagement in physical activity (Chen et al, 2022;Leung et al, 2014). Earlier systematic reviews presented inconsistent results between the environmental correlates of physical activity.…”
Section: Impact Of Individual-level Factors Versus Neighborhood-level...mentioning
confidence: 99%